Résistances tacites face à la requalification d’un quartier urbain en voie de gentrification : Regard à partir du quartier Le Maupas, Lausanne. - May Du (VertigO)
« Le Maupas » is part of the city of Lausanne. Because of some precursory signs, this neighbourhood is considered to be in the process of gentrification. This article deals with a praxeologic approach. It involves a dynamic conception of the urban public spaces and of gentrification. Studying the culture, the mobility and the conviviality features of « le Maupas », I try to highlight how social uses of urban settings manage resistance to change.